Delivering Services in Multicultural Societies - Marc, Alexandre (World Bank, 2012)
The last two decades have witnessed a growing recognition of the importance of taking cultural and ethnic diversity into consideration when designing and implementing development programs. As societies around the world have become more culturally diverse, and the role culture plays in the formation of identity has become better understood, governments are beginning to pay greater attention to the management of cultural diversity and are becoming more sensitive to issues of cultural exclusion. This book explores how taking cultural diversity into account can affect the delivery of services both positively and negatively, and how local governments can respond to the challenge of programming for and around diversity. The following chapter presents the current debate on the role of governments, at all levels, in managing cultural diversity. Chapter three takes a more in-depth look at specific areas in which the demand for recognition of cultural practices in the delivery of services is strongest. Chapter four examines policies pertaining to basic service delivery that can address and support cultural diversity. Finally, chapter five summarizes the lessons learned from the design of culturally sensitive policies for delivering services to a diverse population.